American Babylon christianity and democracy before and after Trump - Gorski, Philip S. 1963- (Routledge, 2020)
Introduction: American Babylon? -- Part I: Elective affinities: Christianity and democracy in Western history -- 1 Is democracy Christian? -- Prologue: "elective affinities" -- Christian ethics and democratic politics -- The four layers of Western democracy -- Republican democracy -- Representative democracy -- Liberal democracy -- The fourth layer: social democracy -- Conclusion: democracy and religion -- Note -- References -- 2 Is Christianity democratic? -- Ancient Israel: covenants and kings -- The early Christians: siblings and patriarchs -- Late antiquity: cities and empires -- The middle ages: popes and councils -- Reformations: communal and magisterial? -- Modernity: revolution or reaction? -- The modern era: dictators and democrats -- Conclusion: sovereign God or triune God? -- References -- Part II: Changing chemistries: Christianity and democracy in American history -- 3 Goodbye Tocqueville? -- Christianity and democracy in Tocqueville's America -- From moral consensus to culture war -- The anti-politics of the apocalypse -- America's churches: from little republics to big firms -- Hello Weber -- References -- 4 The Republican captivity -- Prologue: the "monkey trial" -- The problem: changing affinities -- Foreign policy: from progressive anti-imperialism to American exceptionalism -- Economic policy: from social gospel to CEO Jesus -- Social policy: from Hatrack to Roe v. Wade -- White supremacism: the fourth leg -- Conclusion: Babylonian captivity or Republican captivity? -- References -- 5 White Christian nationalism -- Why did (white) evangelicals vote for Trump? -- Evangelicalism and white Christian nationalism -- White Christian nationalism: a brief history -- Trumpism as white Christian nationalism
Keywords: Trump, Donald -- 1946-; Demokratie; Christentum; USA